Distinct Tropospheric and Stratospheric Mechanisms Linking Historical Barents‐Kara Sea‐Ice Loss and Late Winter Eurasian Temperature Variability. Issue 20 (15th October 2021) - Xu, Mian; Tian, Wenshou; Zhang, Jiankai; Screen, James A.; Huang, Jinlong; Qie, Kai; Wang, Tao
Abstract: Reduced Arctic sea‐ice has been proposed to induce severe Eurasian cold events. However, the physical mechanisms for this connection, particularly the relative importance of tropospheric and stratospheric processes, remain unclear. Using ERA‐Interim reanalysis data and WACCM‐SC simulations, we show that the Eurasian cooling induced by reduced sea‐ice centers over eastern Asia and northern Europe. Tropospheric and stratospheric processes contribute roughly equally to the cooling over eastern Asia, while the stratospheric and tropospheric contributions are 60% and 40%, respectively, over northern Europe. In the tropospheric pathway, weakened meridional temperature gradient due to reduced sea‐ice strengthens the Ural blocking and enhances the Siberian High. The enhanced Siberian High favors two streams of cold air‐mass, reaching northern Europe and eastern Asia. In the stratospheric pathway, enhanced upward‐propagating planetary wave 1 causes a shift of the stratospheric polar vortex toward Eurasia and consequently, tropospheric cyclonic anomalies are induced that enhance surface cold anomalies. Plain Language Summary: Recent years of below‐average Arctic sea‐ice have been proposed to be linked to severe cold winters over Eurasia. However, the causality and mechansims of this connection are unclear. Two general pathways have been proposed through which reduced sea‐ice could induce cold winter, namely, the tropospheric and stratospheric pathways. Here, we sought to measure the relative importance of stratospheric and tropospheric processes in this connection. Using observations and model simulations, we find that distinct tropospheric and stratospheric mechanisms contribute roughly equally to the Eurasian winter cooling in response to reduced sea‐ice. In the tropospheric pathway, we find that the Siberian High, an important surface high pressure system for Eurasian winter climate, is enhanced by the reduced Arctic sea‐ice. This favors the intrusion of cold polar air‐mass into Eurasia. In the stratospheric pathway, the stratospheric polar vortex, a strong wintertime circumpolar westerly system (∼15–40 km), is shifted toward Eurasia by the reduced sea‐ice, which also favors the cold anomalies over Euraisa. Key Points: Distinct tropospheric and stratospheric pathways are equally important for late winter Eurasian cooling in response to Arctic sea‐ice loss Reduced sea‐ice strengthens the Siberian High and induces two cold air‐mass streams over Eurasia independent of stratospheric processes Sea‐ice‐induced extension of stratospheric polar vortex toward eastern Asia and north Europe leads to the cooling over the two regions